A palladium(II)–saccharinate complex of terpyridine exerts higher anticancer potency and less toxicity than cisplatin in a mouse allograft model. Issue 8 (September 2017) - Cetin, Yuksel; Adiguzel, Zelal; Polat, Hivda U.; Akkoc, Tolga; Tas, Arzu; Cevatemre, Buse; Celik, Gokalp; Carikci, Baris; Yilmaz, Veysel T.; Ulukaya, Engin; Acilan, Ceyda
Abstract : The main aim of this study is to assess the safety and antitumor efficacy of a palladium(II) (Pd)–saccharinate complex with terpyridine. To characterize the Pd(II) complex in vitro, its cytotoxicity was evaluated using a water-soluble tetrazolium salt cell viability assay and the mechanism of cell death was assessed by DNA fragmentation/condensation and live cell imaging analyses. The antitumor efficacy and safety of the Pd(II) complex in-vivo were examined by analyzing reduction in tumor size, changes in body and organ weight, histopathological analysis of liver, kidney, and tumor sections, and biochemical analysis of serum in C57BL/6 mice. Our results showed that the Pd(II) complex was more cytotoxic to cancer cells than noncancer cell lines and caused cell death through apoptotic pathways. The treatment of the Pd(II) complex in tumor-bearing mice effectively reduced the tumor size at half the dose used for cisplatin. The Pd(II) complex appeared to exert less liver damage than the cisplatin-based complex on changes in the hepatic enzymes levels in the serum. Hence, the complex appears to be a potential chemotherapeutic drug with high antitumor efficacy and fewer hepatotoxic complications, providing an avenue for further studies.